Availability of informal caregivers in surviving stroke patients in Belgium. Issue 4 (4th November 2013) - Francois, Silke; Borgermans, Liesbeth; Van Casteren, Viviane; Vanthomme, Katrien; Devroey, Dirk
<x xml:space="preserve">Abstract</x> Objective To quantify the availability of informal caregivers in surviving stroke patients residing at home in Belgium. Methods National estimates on the availability of informal caregivers were made using data from a nationwide observational registration of family physicians working in sentinel practices and a nationwide administrative database for reimbursement of hospitals in Belgium. Results A total of 189 Belgian family physicians (FPs) from 141 practices participated in the study and recorded 326 patients (144 men and 182 women) with stroke. These FPs reach 1.5% of the Belgian population. After 1 month, 71% of the male and 75% of the female stroke survivors received support from family caregivers (p = 0.547). After 6 months, the percentage of male patients who received support from family caregivers decreased to 60% compared with 75% in female (p = 0.038). Of all patients with stroke admitted to Belgian hospitals during the reference year 2009 (n = 16.437), 8.997 returned home. Based on the findings from the sentinel practices, it is estimated that a mean of 73% (n = 6.568) and 67.5% (n = 6.073) of surviving patients with stroke can rely on informal caregivers in their home setting after one and 6 months, respectively. Conclusions A vast majority of surviving stroke patients in Belgium can rely on informal caregivers in their home setting, but their availability rapidly decreases 6 months after the event. These findings underline the importance of proactive health policy making in stroke care taking into account the potentially decreasing number of available informal caregivers in the decades to come.